A Case Series on Natural Conceptions Resulting in Ongoing Pregnancies in Menopausal and Prematurely Menopausal Women Following Platelet-Rich Plasma Treatment. Issue 9 (September 2019) - Pantos, Konstantinos; Simopoulou, Mara; Pantou, Agni; Rapani, Anna; Tsioulou, Petroula; Nitsos, Nikolaos; Syrkos, Stephen; Pappas, Athanasios; Koutsilieris, Michael; Sfakianoudis, Konstantinos
Since the introduction of autologous platelet-rich plasma (PRP) in medical practice, various studies have documented that implementing PRP can enhance healing and the anti-aging process, employing angiogenesis regeneration due to the multiple growth factors and cytokines involved. Numerous reports have shown promising results with the use of PRP in ovarian treatment, regarding ovarian regeneration and reactivation of folliculogenesis. This case series reports on two women with premature ovarian failure (POF) aged 40 and 27 years, respectively, and one menopausal woman aged 46 years. All patients presented with lack of menstrual cycle for over a year. The women reported previous failed in vitro fertilization (IVF) attempts, and, after rejecting the option of oocyte donation, they opted for the approach of autologous ovarian PRP treatment. Following PRP treatment, the three patients were invited to conceive naturally. The primary outcome was the restoration of menstruation following autologous ovarian PRP treatment, as well as an improvement in hormonal profile, a decrease in follicle-stimulating hormone (FSH) levels, and a concurrent increase in anti-Müllerian hormone (AMH) levels. Further to that, our patients achieved pregnancy through natural conception within 2–6 months following PRP treatment, resulting in currently ongoing complication-free clinical pregnancies – a first report in the literature for menopausal and POF patients. Implementation of PRP should be further investigated through randomized controlled trials (RCTs), as it may hold the key to successful treatment for a certain cohort of patients exploring reproductive treatment options following menopause.